Entrepreneurial Characteristics’ Influence on Sales Growth for Women-Led SMEs in the Context of the Gaza War: The Moderating Role of Business Intelligence - Abu Khatro, Lama; lafi, Ziad; Rezeq, Mohanad (Ahliya Journal of Business Technology and MEAN Economies, 2024)
This study aims to explore the impact of entrepreneurial characteristics on sales growth among female small business owners in the context of the Gaza conflict. An Analytical Model was used to examine the relationship between entrepreneurial traits such as innovation, leadership, and the ability to face challenges, and the increase in revenues and profitability through a distributed questionnaire and its measured results. The study’s findings indicate that entrepreneurial traits play an important role in enhancing sales growth, as data showed that innovation and leadership are positively associated with increased revenues. However, business intelligence did not significantly impact sales growth, suggesting that other factors may be more influential in this context. The study recommends supporting entrepreneurial skill development programs for Palestinian businesswomen and promoting an entrepreneurial culture in Palestinian society. The originality of this research lies in its focus on exploring the impact of entrepreneurial characteristics on sales growth specifically among female small business owners in the unique context of the Gaza conflict. While much of the existing literature focuses on general factors affecting small business growth, this study sheds light on how traits such as innovation, leadership, and the ability to face challenges specifically contribute to the success of women-led small businesses in a region marked by conflict and economic instability.